A Review on Feasible and Reliable Underwater Wireless Optical Communication System for achieving High Data Rate and Longer Transmission Distance - Lenin Joseph; Sangeetha Anandan (International Journal of Electronics and Telecommunications, 2022)
Underwater Wireless Optical Communication (UWOC) offers significant research prospective with major challenges in the design and implementation. UWOC is capable of providing high rate of data transmission across large distances. This paper attempts to focus on the intricacies of practical implementations and open research issues of UWOC systems. Critical advances and progresses made in the field, modelling techniques and link design challenges are summarised. The purpose of this review is to give suggestions towards feasible and reliable UWOC design with improved performance. Finally the major points are summarized so that it will assist the future research in UWOC.